Research on desktop 3D Printing Multi-Material New Concepts. Issue 1 (October 2021) - Fenollosa, F; Uceda, R; Tejo, A; Calvo, L; Poudelet, L; Buj, I
Abstract: 3D printing or Additive Manufacturing (AM) was originally born as a mono-material technology. And, nowadays, most of the applications are still using only one material. AM has a lot of potential but has not yet been fully explored, and access to the creation of multi-material products is an example of it. One of the most interesting areas is the introduction in the same part of materials with different rigidities, stiffer and softer areas, with differentiated values of mechanical strength and viscoelasticity. In the present work, a general vision of Additive Manufacturing under the vision of mono- and multi-material processes is given, and some existing 3D printing multi-material experiences related to Material Jetting (MJ) and Material Extrusion (ME) are briefly described. But it is in this latter field, linked to Desktop 3D printing (more accessible than typical proprietary industrial equipment), where on-going research could easily be spread: five research ME concepts are then presented, from a revolver print-head to silicone UV 3D printing, with their initial embodiment in the form of prototypes or/and testing, as a way to verify the difficulties that would be encountered in the transition from research to reality.